Extractive Spectrophotometric Determination of Cobalt(II) with benzildithiosemicarbazone - Krishna Reddy, B.; Jaya Kumar, C.; Subramanyam Sarma, L.; Varada Reddy, A. (Asian Journal of Chemistry, 2010)
An extractive spectrophotometric method for the determination of cobalt(II) using benzildithiosemicarbazone is reported. The cobalt(II)-benzildithiosemicarbazone complex with a molar absorptivity of 7.329 x 103 L mol–1 cm–1 and Sandell's sensitivity of 0.008044 μg/cm2 obeys Beer's law in the range 1.0-8.0 ppm of cobalt(II). The instability constant of the complex is determined. The effect of various diverse ions in the determination of cobalt(II) is studied. The method is successfully applied for the determination of cobalt(II) in medicinal and beer samples and the results are compared with atomic absorption spectrophotometer.